Deciphering Behavioural factors influencing the decision making of investors: A TISM- MICMAC approach (Journal of Informatics Education and Research, 2025)
This study aims to investigate recent advancements in behavioural finance, specifically focusing on the presence of behavioural biases that influence investors' decision-making processes. Additionally, it assesses the feasibility of behavioural finance as a widely recognized evolution beyond traditional finance. By investigating the cognitive and emotional biases that influence individual investors during the process of making investment decisions and their portfolio choices, this study intends to highlight the substantial effect these biases have on investment outcomes. Through a detailed examination of biases, the research seeks to provide a deeper understanding of how these factors contribute to suboptimal decisions, ultimately affecting market efficiency and financial stability.